Arm weight effects on dynamic walking stability in individuals with hemiparetic stroke. - Hyung Suk Yang; Lee T Atkins; C Roger James (PLoS ONE)
This study examined the effects of arm weights on dynamic stability during overground walking in individuals with hemiparetic stroke. Arm weights have been shown to improve mobility in stroke survivors, potentially at the cost of decreased dynamic stability and increased fall risk. Data from nine stroke survivors (8 males, 1 female; age: 58.0 ± 6.8 years) were assessed under four conditions: no weight, weight attached to the non-hemiparetic side, weight attached to the hemiparetic side, and bilateral weights. Each condition used 0.45 kg sandbags. Kinematic data were captured using an eight-camera motion system and analyzed to assess center of mass position and velocity relative to the base of support. Although repeated measures ANOVA showed no significant differences in stability across conditions, individual scatter plots revealed variable responses among participants. Some maintained or improved their stability, while others experienced decreases under specific conditions. These findings underscore the need for personalized approaches in rehabilitation planning, suggesting that integrating arm weights into rehabilitation protocols may not compromise dynamic stability for most stroke survivors. Further research with larger sample sizes and varied weights is essential to validate these findings and tailor the use of arm weights in stroke rehabilitation more effectively.